(untitled) (Educação e Pesquisa, 2010)
Despite the efforts of the proponents of the teaching of Philosophy to have the subject back into the Secondary School curriculum, we watch nowadays its neglect in higher education. We observe that today, in this normalized society and in the educational sphere, the integral development of thinking is no longer valued, in favor of the transmission of a series of contents which supposedly allow the student to fit into the picture of technological progress and gain access to the labor market. Centering on this context, the present text intends to investigate the space in which the teaching of Philosophy evolves today. By sketching the contours of a problem that emerges in the university institutional spaces where the teaching of Philosophy still subsists, we have attempted to bring forward the bases on which Philosophy is taught. We have also sought to understand what are the consequences for the learning of philosophizing of the different ways to understand the teaching of Philosophy. A conclusion warranted by this study is that the teaching of Philosophy not only fails to give priority to the experience of thinking, but often denies the students the opportunity of doing and having this experience with the philosophical text, thereby contributing to impoverish this same experience of and with the philosophizing.